Genomic and Functional Characterization of the Unusual pLOCK 0919 Plasmid Harboring the spaCBA Pili Cluster in Lactobacillus casei LOCK 0919 - Aleksandrzak-Piekarczyk, Tamara; Koryszewska-Bagińska, Anna; Grynberg, Marcin; Nowak, Adriana; Cukrowska, Bożena; Kozakova, Hana; Bardowski, Jacek (Genome biology and evolution, 2015)
Here, we report the extensive bioinformatic and functional analyses of the unusual pLOCK 0919, a plasmid originating from the probiotic Lactobacillus casei LOCK 0919 strain. This plasmid is atypical because it harbors the spaCBA-srtC gene cluster encoding SpaCBA pili. We show that all other spaCBA-srtC sequences of the Lactobacillus genus that have been previously described and deposited in GenBank are present in the chromosomal DNA. Another important observation for pLOCK 0919 is that the spaCBA-srtC gene cluster and its surrounding genes are highly similar to the respective DNA region that is present in the most well-known and active SpaCBA pili producer, the probiotic Lactobacillus rhamnosus GG strain. Our results demonstrate that the spaCBA-srtC clusters of pLOCK 0919 and L. rhamnosus GG are genealogically similar, located in DNA regions that are rich in transposase genes and are poorly conserved among the publicly available sequences of Lactobacillus sp. In contrast to chromosomally localized pilus gene clusters from L. casei and Lactobacillus paracasei, the plasmidic spaC of L. casei LOCK 0919 is expressed and undergoes a slight glucose-induced repression. Moreover, results of series of in vitro tests demonstrate that L. casei LOCK 0919 has an adhesion potential, which is largely determined by the presence of the pLOCK 0919 plasmid. In particular, the plasmid occurrence positively influenced the hydrophobicity and aggregation abilities of L. casei LOCK 0919. Moreover, in vivo studies indicate that among the three Lactobacillus strains used to colonize the gastrointestinal tract of germ-free mice, already after 2 days of colonization, L. casei LOCK 0919 became the dominant strain and persisted there for at least 48 days.
Keywords: Multigene Family; Plasmids; cysteinové endopeptidasy; aminoacyltransferasy; Bacterial Proteins; membránové proteiny; Fimbriae, Bacterial; Genome, Bacterial; Membrane Proteins; molekulární sekvence - údaje; Amino Acid Sequence; Lacticaseibacillus casei; Transposases; transposasy; genom bakteriální; Lactobacillus casei; bakteriální fimbrie; Cysteine Endopeptidases; bakteriální proteiny; plazmidy; sekvence aminokyselin; Molecular Sequence Data; multigenová rodina; Aminoacyltransferases